YAP-induced Ccl2 expression is associated with a switch in hepatic macrophage identity and vascular remodelling in liver cancer - Thomann, Stefan; Weiler, Sofia Maria Elisabeth; Wei, Teng; Sticht, Carsten; Torre, Carolina de la; Tóth, Marcell; Rose, Fabian; Tang, Yingyue; Ritz, Thomas; Ball, Claudia; Glimm, Hanno; Ryschich, Eduard; et al. (Liver international, 2021)
Background & aim The development of hepatocellular carcinoma (HCC) is associated with the formation of communication networks leading to the recruitment of disease-modifying macrophages. However, how oncogenes in tumour cells control paracrine communication is not fully understood. Methods Transgenic mice with liver-specific expression of the constitutively active yes-associated protein (YAPS127A) or an orthotopic implantation model served as tumour models. FACS-sorted F4/80+/CD11bdim/CD146-/retinoid- macrophages from healthy and tumour-bearing livers were used for transcriptomic profiling. Expression data of 242 human HCCs and a tissue microarray consisting of 91 HCCs and seven liver tissues were analyzed. Results Screening of primary tumour cells expressing YAPS127A identified CC chemokine ligand 2 (Ccl2) as a macrophage chemoattractant, whose expression was regulated in a YAP/TEA domain family member 4 (TEAD4)-dependent manner. Ccl2 expression was associated with a loss of Kupffer cells (KCs) and an increase in immature macrophages (Mɸimm) in hepatocarcinogenesis. Recruited Mɸimm were characterized by a lack of functional polarization (M0 signature) and high expression of the Ccl2 receptors C-C motif chemokine receptor 2 (Ccr2), C-X3-C motif chemokine receptor 1 (Cx3cr1) and pro-angiogenic platelet-derived growth factors (Pdgfa/Pdgfb). Mɸimm formed cellular clusters in the perivascular space, which correlated with vascular morphometric changes indicative for angiogenesis. In human HCCs, the M0 signature served as an identifier for poor clinical outcome and CCL2 correlated with YAP expression and vascular network formation. Conclusions In conclusion, YAP/TEAD4-regulated Ccl2 associates with perivascular recruitment of unpolarized Mɸimm and may contribute to a proangiogenic microenvironment in liver cancer.